Here's Hoping It's not Just Text Structure: The Role of Emotions in Knowledge Revision and the Backfire Effect. Issue 1 (7th February 2022) - Jacobson, Neil G.; Thacker, Ian; Sinatra, Gale M.
ABSTRACT: Refutation texts are designed to facilitate the revision of inaccurate knowledge; however, studies have documented backfire effects wherein respondents become less accurate when exposed to a factual correction compared to another. Here, we explored whether epistemic emotions mediated knowledge revision or backfire processes when reading experimental refutation texts that varied by supporting information. We asked 294 online readers to report their knowledge and attitudes about genetically modified foods before randomly assigning them to one of three refutation text conditions which varied in type of supporting information. We documented relatively low knowledge (19.7%) and attitude (14%) backfire across conditions and found no evidence of backfire effects among types of supporting information. All texts facilitated knowledge revision regardless of the type of supporting information but did not differentially elicit epistemic emotions. For those who revised their inaccurate knowledge, hope and surprise mediated the knowledge revision process. However, those who demonstrated a backfire effect reported significantly more anger and confusion than readers who revised their inaccurate knowledge. Implications for research and practice are discussed.